PENANAMAN DAN IMPLEMENTASI NILAI PENDIDIKAN MULTIKULTURAL (STUDI KASUS DI UNIVERSITAS MUHAMMADIYAH GORONTALO) - Sriwahyuningsih R Saleh; Chaterina Puteri Doni (Education Journal : Journal Educational Research and Development, 2018)
A country with diverse societies will be particularly vulnerable to a conflict. Indonesia is a country that has a situation that is faced with problems that are not light. It takes this thing so that all components can hiudp safely, comfortably, comfortably and peacefully for the life of society, nation and state. However, this beloved nation of Indonesia is still covered by various koflik that appear in the community. The community needs to be equipped with various knowledge about the state of banggsanya early on. Education is the right thing to cultivate a variety of attitudes that support the creation of peace. Islamic education in Indonesia has become a pillar of nationality. For that how the education of Islam, especially education that is located in Islamic religious institutions seeking to realize a multicultural education in planting and implementation. With a multicultural-based education process, at the university level will provide opportunities to lecturers, students and the community environment to always there will be differences. At that time, the opportunity to appreciate, appreciate, and give support to different parties, will be the beginning of the planting and implementation of a multicultural.